Schottky contacts on ultra-high-pressure-annealed GaN with high rectification ratio and near-unity ideality factor. (1st March 2023) - Stein, Shane R.; Khachariya, Dolar; Mita, Seiji; Breckenridge, M. Hayden; Tweedie, James; Reddy, Pramod; Sierakowski, Kacper; Kamler, Grzegorz; Boćkowski, Michał; Kohn, Erhard; Sitar, Zlatko; Collazo, Ramón; et al.
Abstract: We investigate the electrical characteristics of Ni Schottky contacts on n-type GaN films that have undergone ultra-high-pressure annealing (UHPA), a key processing step for activating implanted Mg. Contacts deposited on these films exhibit low rectification and high leakage current compared to contacts on as-grown films. By employing an optimized surface treatment to restore the GaN surface following UHPA, we obtain Schottky contacts with a high rectification ratio of ∼10 9, a near-unity ideality factor of 1.03, and a barrier height of ∼0.9 eV. These characteristics enable the development of GaN junction barrier Schottky diodes employing Mg implantation and UHPA.